FATP4 contributes as an enzyme to the basal and insulin-mediated fatty acid uptake of C2C12 muscle cells - Digel, Margarete; Staffer, Simone; Ehehalt, Friedrich; Stremmel, Wolfgang; Ehehalt, Robert; Füllekrug, Joachim (American journal of physiology. Endocrinology and metabolism, 2011)
The function of membrane proteins in long-chain fatty acid transport is controversial. The acyl-CoA synthetase fatty acid transport protein-4 (FATP4) has been suggested to facilitate fatty acid uptake indirectly by its enzymatic activity, or directly by transport across the plasma membrane. Here, we investigated the function of FATP4 in basal and insulin mediated fatty acid uptake in C2C12 muscle cells, a model system relevant for fatty acid metabolism. Stable expression of exogenous FATP4 resulted in a twofold higher fatty acyl-CoA synthetase activity, and cellular uptake of oleate was enhanced similarly. Kinetic analysis demonstrated that FATP4 allowed the cells to reach apparent saturation of fatty acid uptake at a twofold higher level compared with control. Short-term treatment with insulin increased fatty acid uptake in line with previous reports. Surprisingly, insulin increased the acyl-CoA synthetase activity of C2C12 cells within minutes. This effect was sensitive to inhibition of insulin signaling by wortmannin. Affinity purified FATP4 prepared from insulin-treated cells showed an enhanced enzyme activity, suggesting it constitutes a novel target of short-term metabolic regulation by insulin. This offers a new mechanistic explanation for the concomitantly observed enhanced fatty acid uptake. FATP4 was colocalized to the endoplasmic reticulum by double immunofluorescence and subcellular fractionation, clearly distinct from the plasma membrane. Importantly, neither differentiation into myotubes nor insulin treatment changed the localization of FATP4. We conclude that FATP4 functions by its intrinsic enzymatic activity. This is in line with the concept that intracellular metabolism plays a significant role in cellular fatty acid uptake.
Gesehen am 10.06.2022